[Students Dining During Welcome Week] (1950)
Students dining at Camp Ocean Pines during Welcome Week activities. Students are wearing hats with elephant cutouts with names and "The Herd" handwritten. Sign that reads "Invitation to Thought" Coffee Luncheon.